Development of a calcifying fibrous pseudotumour within a lesion of Castleman disease, hyaline-vascular subtype. - Dargent, J L (1999)
A nine year old boy with localised Castleman disease of the hyaline-vascular subtype developed a calcifying fibrous pseudotumour. This pathological association does not appear to have been described before. In this case, the development of this very unusual soft tissue tumour-like process was thought to be related to a previous fine needle aspiration biopsy, which was performed because of lymphadenopathy localised to the right inguinal area. This case provides further evidence of the reactive nature of calcifying fibrous pseudotumour and also broadens the pathological spectrum of the stromal cell proliferation that occasionally supervenes within lesions of Castleman disease, hyaline-vascular type.